2015
DOI: 10.4103/1119-3077.151039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hemostatic agents on shear bond strength of orthodontic brackets

Abstract: In impacted tooth surgical operations, blood contamination poses a substantial risk of bond failure in bonding attachments applications to the impacted teeth. Epinephrine and ABS may be used on surgical exposed impacted teeth operation for the prevention of blood contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Studies have shown that for both total-etch and self-etch adhesives, the SBS of the contaminated dentin surface is re-established by performing etching with phosphoric acid [40]. Other studies have reported lower SBS with phosphoric acid [12]. Because of its acidity (pH=-0.7), 37% phosphoric acid induces limited denaturation of the uncovered matrix metalloproteinases (MMPs) [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that for both total-etch and self-etch adhesives, the SBS of the contaminated dentin surface is re-established by performing etching with phosphoric acid [40]. Other studies have reported lower SBS with phosphoric acid [12]. Because of its acidity (pH=-0.7), 37% phosphoric acid induces limited denaturation of the uncovered matrix metalloproteinases (MMPs) [46].…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to contaminants during clinical procedures is inevitable, impacting the tooth-restoration interface [12]. These contaminants, present in saliva, blood, gingival crevicular fluid, and hemostatic agents, can significantly compromise bond strength [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this surgical operation, providing moisture control is more crucial due to blood contamination. Studies showed that contamination of blood and/or saliva has a negative effect on bonding of orthodontic attachments (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of microleakage can result in tooth sensitivity, recurrent caries, irritation of the pulp and failure of treatment (6). Therefore, in order to improve the quality of restoration and increase their longevity, attempts should be made to control bleeding and gingival crevicular fluid; a technique to achieve this is the use of hemostatic agents (7-9). Aluminum chloride is one of the hemostatic agents that is used to this end.…”
Section: Introductionmentioning
confidence: 99%